Development of a Pocket Book on Effective Communication Using Chain Message Games for Vocational High School Students - Adinda Hariana Safitri; Nefi Darmayanti (International Journal of Applied Guidance and Counseling, 2026)
This study aimed to develop an effective communication pocketbook based on the Chain Message Game as a supporting medium for group guidance services and to determine its feasibility and practicality. The study employed the Research and Development method using the Four-D development model through the define, design, and develop stages. The needs analysis indicated a need level of 90.26%. Media expert validation obtained 91.9%, while material expert validation obtained 90.9%, both categorized as highly feasible. The guidance and counseling teacher response reached 92.6%, while the student response reached 93.4%, indicating a very high level of practicality. The novelty of the product lies in integrating effective communication materials, the Chain Message Game, and reflective activities into a concise and interactive medium. The results indicate that the product is feasible and practical as a supporting medium for group guidance services. However, its effectiveness in improving students’ communication skills has not yet been tested; therefore, future research should conduct experimental testing.